Putting into Practice Gap Tasks in an ESP Classroom for Medicine Personnel at Universidad de Costa Rica - Villanea Morales, Lucía (Universidad de Costa Rica, 2018)
This paper presents the results of a study conducted in a group of eight students in an ESP course taught by Practicum students at the School of Medicine at the University of Costa Rica. The results indicate that the student-teachers based their lessons mostly on information gap tasks. Besides, this study revealed that the activities presented followed a common pattern avoiding variety.  In addition, the study reflected that the activities used during the days of observation, did not fulfilled the requirements of a good gap task in a hundred percent since the tasks did not promote spontaneous and creative communication.   The correct use of gap tasks helps students to develop speaking skills in a safe and private environment. The outcomes of these kinds of tasks will always be positive as long as they are adequate, relevant, authentic, and achievable.